(untitled) (International Seven Journal of Health Research, 2023)
The World Health Organization, in 2008, revealed that 234 million operations were performed worldwide, which is equivalent to one surgery for every 25 people alive in the world¹. Among them, about 5% had complications, and 50% of them were considered¹. What is the perioperative period is defined as the period that involves the surgical act from the previous preparation to recovery and discharge. It starts when the surgeon indicates the operation until the patient returns to his or her normal activities². The perioperative period involves the preoperative, transoperative, and postoperative phases, each with its own specificities³. The importance of the period and its understanding is due to the fact that it aims to improve the lives of patients, acting therapeutically, but it presents risks and potential complications if each step is not well performed.